2005
DOI: 10.1038/ni1220
|View full text |Cite
|
Sign up to set email alerts
|

Nonstimulatory peptides contribute to antigen-induced CD8–T cell receptor interaction at the immunological synapse

Abstract: It is unclear if the interaction between CD8 and the TCR-CD3 complex is constitutive or antigeninduced. FRET microscopy between fluorescent chimeras of CD3ζ and CD8β showed that this interaction was induced by antigen recognition, within the immunological synapse. Non-stimulatory endogenous or exogenous peptides, presented simultaneously with antigenic peptides, increased the CD8-TCR interaction. This indicates that the interaction between the intracellular regions of a TCR-CD3 complex recognizing its cognate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
190
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(209 citation statements)
references
References 49 publications
12
190
2
Order By: Relevance
“…S3), this argues that the density of cytoskeletonassociated ICAM-1 modulates the mobility of noncognate complexes in the synapse. 2) CD8 in the synapse can bind to and retain noncognate MHC I-peptide complexes (47). These authors proposed that CD8 increases the local density of MHC I-peptide complexes in the synapse and vice versa and that this enhances the sensitivity of antigen recognition.…”
Section: Discussionmentioning
confidence: 99%
“…S3), this argues that the density of cytoskeletonassociated ICAM-1 modulates the mobility of noncognate complexes in the synapse. 2) CD8 in the synapse can bind to and retain noncognate MHC I-peptide complexes (47). These authors proposed that CD8 increases the local density of MHC I-peptide complexes in the synapse and vice versa and that this enhances the sensitivity of antigen recognition.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, SCTs were used to demonstrate the importance of size-based molecular segregation for immune synapse formation (54). Along these same lines, a future application of SCTs should be to definitively test the importance of non-cognate co-receptor interactions in immune synapses (55). Finally SCTs have been expressed as transgenes and used to define MHC-I-mediated licensing during NK cell development (49).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the T cell activation thresholds for such weak ligands may be enhanced by the repertoire of self-peptides present on an APC. Recent reports with both CD4 + and CD8+ T cells have suggested that normal self peptides contribute towards the formation of an immunological synapse and T cell activation [44,45]. The extent and specificity of these self peptide-MHC complexes in facilitating activation of antigen-specific T cells needs to be examined in greater detail.…”
Section: Weak Mhc Binding Peptides and Autoreactivity: The Case Of Thmentioning
confidence: 99%